Approximation classes for adaptive higher order finite element approximation - Gaspoz, Fernando Daniel (2014)
We provide an almost characterization of the approximation classes appearing when using adaptive finite elements of Lagrange type of any fixed polynomial degree. The characterization is stated in terms of Besov regularity, and requires the approximation within spaces with integrability indices below one. This article generalizes to higher order nite elements the results presented for linear nite elements by Binev et. al.